Effect of Spiritual Cognitive Therapy on Decreasing the Depression Level among Elderly at Nursing Home - Ratna Sari Rumakey; Retno Indarwati; Merryana Andriani (International Journal of Nursing and Health Services (IJNHS), 2020)
Depression in the elderly with age> 65 can cause dysfunction in everyday life, older people with depression have a worse function than the elderly with chronic conditions. This study aims to identify the effect of cognitive, spiritual therapy on decreasing depression in the elderly in nursing homes. A quasi-experimental pre and post-test with an equivalent control group were applied in this study. Sixty-one older people were selected in this study using a simple random sampling technique. The results showed there was a significant influence of spiritual, cognitive therapy on depression (p=0.000). In conclusion, spiritual, cognitive therapy affects reducing depression in the elderly